Experimental study of triaxial shear features of concentrated full tailings considering the effect of curing age - Wang, Sha; Mei, Guodong; Wang, Weixiang; Wang, Yali; Cui, Yiyuan; Guo, Lijie; Chu, Yifan (Frontiers in Earth Science, 2023)
This study aims to investigate the influence of curing materials on the shear strength of full tailings and reveal the change law of the shear strength of concentrated full tailings with the curing age. Therefore, we carried out a comparative triaxial shear test between pure full tailings and concentrated full tailings with different curing ages. The test results show that concentrated full tailings had a 70.7% higher cohesion and a 10% larger internal friction angle (IFA) than that of pure full tailings at the age of 0 d. Moreover, the concentrated full tailings cured for 3 d had a 170.2% higher cohesion and a 12.1% larger IFA than that cured for 0 d. In addition, the concentrated full tailings cured for 7 d had a 149.4% higher cohesion and a 12.1% larger IFA than that cured for 0 d. The stress-strain curve exhibits that the shear strength of full tailings is significantly influenced by the curing material and curing age. The stress-strain curve gradually moved from strain hardening to strain softening as the curing age increased, and the failure curve had two steps. This indicates that the specimen still has a certain shear capacity despite having a shear zone. The entire specimen instantly fails when the strain exceeds that capacity. The results of this study can be used as scientific bases for the design and construction of the surface storage structures of concentrated full tailings.